GENDER DALAM HUKUM ADAT - Sukerti, Ni Nyoman (Jurnal Studi Jender SRIKANDI, 2012)
The national government of Indonesia is committed to legal gender equality by the1945 Indoensia Constitution, article 27 (1), and the ratification of the Convention forElimination of all forms of Discrimination Against Women (CEDAW) in 1984.However, customary law still prevailing in many regions in Indoneia oftenperpetuates deeply rooted discrimination based on gender until today. Examples ofsuch discrimination are to found in Minagkabau, Java, and Bali where inheritance isregulated by gender biased customary law. Appropriate development policies andeducation may bring about a legal culture and practice that upholds legal genderequality.